The rise of Western Christendom : triumph and diversity AD 200-1000 - Brown, Peter 1935- (Malden, MA : Blackwell Publishers, 1997)
A history of the people, struggles, defeats and victories, ideas and actions that together comprise the history of the first 1000 years of Christianity. The book ranges across the whole of Asia Minor, North Africa and Europe. It describes, too, the rise of Islam and its effect on Christianity.
The laws of countries" --
Christianity and empire --
Tempora Christiana: Christian times --
Virtutes Sanctorum ... Strages Gentium: "Deeds of Saints ... Slaughter of nations" --
On the frontiers: Noricum, Ireland and Francia --
Reverentia, Rusticitas: Caesarius of Arles to Gregory of Tours --
Bishops, city and desert: East Rome --
Regimen Animarum: Gregory the Great --
Medicamenta Paenitentiae: Columbanus --
Christianity in Asia --
"The changing of the kingdoms:" Christians under Islam --
Christianities of the North: Ireland and Saxon Britain --
Micro-Christendoms --
The crisis of the image: The Byzantine iconoclast controversy --
Closing the frontier: Frisia and Germany --
"To rule the Christian people:" Charlemagne --
In Gear Dagum: "In days of yore" --
Northern Christendom and its past.
Keywords: Church History -- Primative and early church; Church History -- Western church -- Middle ages